Stress and Anxiety on the Road: The Silent Victims and Their Sufferings - Nuura Addina Mohamad, (Journal of Advanced Vehicle System, 2022)
This paper explores the issue of stress and anxious behaviour among frequent drivers. Driver Stress Inventory and Anxious Driving Behaviour scales were adopted to probe private car vehicle drivers through an online survey. Driver samples were obtained within the vicinity of three states in Malaysia which are Selangor, Putrajaya and Kuala Lumpur. Analysis suggests that hazard monitoring particularly on difficult road stretch and pedestrian are the main source of driving stress while exaggerated safety/caution behaviour involving bad weather and driving speed adjustment are the most frequently exhibited form of anxious driving behaviour. Narrowing down into hazard monitoring and exaggerated safety/caution behaviour, findings suggest that older age, longer driving distance and higher income level contribute to level of stress while trauma due to past history of crash involvement affect the level of anxiety while driving. The findings highlight that road environments and weather condition can influence driver stress and anxiousness. Further studies are needed to establish the extend of impact from stress and anxiety but improving road infrastructure to segregate vulnerable road users and increase visibility may help in curbing problems related to road stress and anxiety among drivers.